2020
DOI: 10.1182/blood.2019003664
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genetic testing in adults with HLH reveals an inflammatory profile rather than a cytotoxicity defect

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory condition. Primary HLH occurs early in life due to monogenic biallelic mutations affecting lymphocyte cytotoxicity. Secondary HLH occurs mostly in adults secondary to infections, lymphoma or rheumatic diseases. In this latter setting, lymphocyte cytotoxicity status is not known. We conducted a systematic evaluation of NK cell cytotoxicity in adult patients with secondary HLH. Adult patients with secondary HLH were prospectively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…Clinically, HLH is a systemic disease characterised by persistent fever, progressive cytopenias and multi-organ dysfunction caused by an uncontrolled immune activation associated with excessive cytokine production [ 3 ]. Immunopathologically, HLH is characterised by a decreased capacity of interferon gamma production and an activated NK phenotype profile (increased CD69, ICAM-1, HLADR, CCR5 expression) similar to other hyperinflammatory diseases [ 4 ]. CD163 macrophages are involved in hyperferritinaemic syndromes given their role in reticuloendothelial iron signalling, hence sHLH is also known as macrophage activation syndrome (MAS) especially in paediatric literature [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, HLH is a systemic disease characterised by persistent fever, progressive cytopenias and multi-organ dysfunction caused by an uncontrolled immune activation associated with excessive cytokine production [ 3 ]. Immunopathologically, HLH is characterised by a decreased capacity of interferon gamma production and an activated NK phenotype profile (increased CD69, ICAM-1, HLADR, CCR5 expression) similar to other hyperinflammatory diseases [ 4 ]. CD163 macrophages are involved in hyperferritinaemic syndromes given their role in reticuloendothelial iron signalling, hence sHLH is also known as macrophage activation syndrome (MAS) especially in paediatric literature [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric primary HLH is mostly caused by genetic mutations in genes involved in lymphocyte cytotoxicity [5][6][7][8]. In contrast, the analysis of adult HLH has highlighted the absence of a lymphocyte cytotoxicity defect [9].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted therapy is based on the HLH-2004 protocol [18][19]. However, acquired adult HLH and primitive pediatric HLH are two different diseases, with non-comparable pathophysiology [9]. In addition, systematic immunosuppressive therapy on fragile ICU patients could aggravate their condition and expose them to a high risk of infection [20].…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Previous studies reported higher prevalence of the A91V variant in HLH patients. 13 , 14 It is reasonable to think that perforin bearing the A91V change could be related to suboptimal activation and effector capacities of CD8 and/or natural killer (NK) cells. In the context of a viral infection, the correct function of these cells is required to contain the viral replication, clear the virus and overcome the infection.…”
mentioning
confidence: 99%